Cathodic Protection of Carbon Steel Using Aluminum as Sacrificial Anode in Sea Water - Hamad, Muayad Fadhil (Nahrain University College of Engineering Journal, 2015)
The effect of Aluminum as sacrificial anode in seawater (3.5% NaCl) of PH=6.8 was investigated under flow conditions (0-0.262 m/s) for a range of temperatures (25-45°C) using rotating cylinder electrode. And different area of Aluminum at distance of 6cmwere used to protect steel from corrosion, these were A1=2*2cm2, A2=4*4cm2 and A3=8*8cm2 under stationary and flow conditions... It is found that the corrosion rate of carbon steel increases with flow velocity when it free and when coupling with Al it has unstable trend with temperature but also the corrosion rate of Fe decreased after coupling. Using small area of Al increase the corrosion rate while using large area will not highly effective on corrosion rate of Fe. The protection percent of Fe increases appreciably (shifts to more positive) with increasing rotation velocity. It shifts to more negative with increasing temperature.